Editor's Choice – External Applicability of the COMPASS and VOYAGER-PAD Trials on Patients with Symptomatic Lower Extremity Artery Disease in France: The COPART Registry. (September 2021) - Lapébie, François-Xavier; Aboyans, Victor; Lacroix, Philippe; Constans, Joël; Boulon, Carine; Messas, Emmanuel; Ferrières, Jean; Bongard, Vanina; Bura-Rivière, Alessandra
Abstract : Objective: The aim of this study was to examine the external applicability of the COMPASS and the VOYAGER-PAD trials in patients with lower extremity artery disease (LEAD) in the real world. Methods: This was a multicentre retrospective analysis of prospectively collected COPART data, a French multicentre registry of patients hospitalised for symptomatic LEAD. The proportion of patients eligible for the combination of rivaroxaban 2.5 mg twice daily plus aspirin based on either COMPASS or VOYAGER-PAD criteria is reported. The one year cumulative incidence of outcomes between eligible and non-eligible patients, as well as eligible patients vs. control arms of the COMPASS (LEAD patient subgroup) and the VOYAGER-PAD trials were compared. Analyses were performed using Cox models. Results: Of 2 259 evaluable patients, only 679 (30.1%) were eligible for a low dose rivaroxaban plus aspirin regimen. Others were not eligible because of the need for anticoagulant (48.5% and 38.9% of patients meeting COMPASS and VOYAGER-PAD exclusion criteria, respectively) or dual antiplatelet therapy use (15.7% and 16.5%, respectively), high bleeding risk (14.4% and 11.6%, respectively), malignancy (26.1% and 21.0%, respectively), history of ischaemic/haemorrhagic stroke (21.1% and 19.8%, respectively), and severe renal failure (13.2% and 10.5%, respectively). COMPASS and VOYAGER-PAD eligible and ineligible patients were at higher risk of ischaemic events than participants in these trials. The one year cumulative incidences were 6.0% (95% CI 4.3 – 8.1) in the COMPASS eligible subset vs. 3.5% (95% CI 2.9 – 4.3) in the COMPASS control arm for major adverse cardiovascular events, and 27.9% (95% CI 19.9 – 38.3) in the VOYAGER-PAD eligible subset vs. 6.0% (95% CI 5.3 – 6.9) in the VOYAGER-PAD control arm for major adverse limb events. Conclusion: Many patients hospitalised for symptomatic LEAD in France are not eligible for the low dose rivaroxaban plus aspirin combination. In turn, those eligible may potentially have greater absolute benefit because of higher risk than those enrolled in the trials.